QUALITY OF LISTENING TEST VALIDITY OF THE NATIONAL LEAVING EXAM FOR SMA - Wuwuh Yunhadi (JARES (Journal of Academic Research and Sciences), 2016)
This study reports quality of content validity of items of listening test of National Leaving Exam for SMA in Samarinda is constructed. The quality was identified from task coverage, item difficulty, objective of item, and test format. This study used content analysis with qualitative design. The study revealed that content validity revealed three major findings. Task coverage is dominated by the first and the second year of SMA (8 items are from first year, 8 items are from second year, and 4 items are from third year of SMA). Of 20 items, 9 (45%) are easy, 7 (35%) moderate, 4 (2o%) hard. The questions in the items are specified into 9 (45%) general, 5 (25%) comprehension, 4 (20%) application, and 2 (10%) analysis. The analysis on the Table of Specification reconstructed from the English listening test showed that the test has low content validity.